2000
DOI: 10.1094/mpmi.2000.13.10.1121
|View full text |Cite
|
Sign up to set email alerts
|

Both Induction and Morphogenesis of Cyst Nematode Feeding Cells Are Mediated by Auxin

Abstract: Various lines of evidence show that local changes in the auxin concentration are involved in the initiation and directional expansion of syncytia induced by cyst nematodes. Analysis of nematode infections on auxin-insensitive tomato and Arabidopsis mutants revealed various phenotypes ranging from complete inhibition of syncytium development to a decrease in hypertrophy and lateral root formation at the infection site. Specific activation of an auxin-responsive promoter confirmed the role of auxin and pointed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
211
6
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(235 citation statements)
references
References 52 publications
11
211
6
2
Order By: Relevance
“…In line with our experimental data, ET biosynthesis and signaling were generally down-regulated in giant cells on Arabidopsis (Barcala et al, 2010). Strikingly, ET has been suggested to be critical for syncytia formation during cyst nematode infections on Arabidopsis (Goverse et al, 2000;Wubben et al, 2001). However, for RKN, Lohar and Bird (2003) found no changes in susceptibility in ET-resistant Lotus japonicus, and the fact that ET was not detected in galls at 1 to 2 d post infection (Glazer et al, 1983) in combination with the transcriptional patterns observed in this study and by Barcala et al (2010) argue against a crucial role for ET-activated pathways during early giant cell differentiation; rather, they suggest that the RKN is actively suppressing the ET pathway and other defense signaling pathways in the root.…”
Section: Discussionsupporting
confidence: 89%
“…In line with our experimental data, ET biosynthesis and signaling were generally down-regulated in giant cells on Arabidopsis (Barcala et al, 2010). Strikingly, ET has been suggested to be critical for syncytia formation during cyst nematode infections on Arabidopsis (Goverse et al, 2000;Wubben et al, 2001). However, for RKN, Lohar and Bird (2003) found no changes in susceptibility in ET-resistant Lotus japonicus, and the fact that ET was not detected in galls at 1 to 2 d post infection (Glazer et al, 1983) in combination with the transcriptional patterns observed in this study and by Barcala et al (2010) argue against a crucial role for ET-activated pathways during early giant cell differentiation; rather, they suggest that the RKN is actively suppressing the ET pathway and other defense signaling pathways in the root.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to nodule initiation, an enhanced auxin response has been visualized at the infection sites of both cyst and root-knot nematodes, whereas auxin signaling mutants have shown significantly lower nematode infection (Hutangura et al, 1999;Goverse et al, 2000;Karczmarek et al, 2004;Grunewald et al, 2008). This suggests that auxin might trigger the initiation of both giant cells and syncytia and that auxin-dependent programs are needed for NFS establishment.…”
Section: Nematode Infection Requires Changes In the Host's Auxin Respmentioning
confidence: 94%
“…Indeed, when lateral auxin transport was inhibited chemically or genetically, radial expansion of the syncytial cell was inhibited, and small malformed cysts were produced (Goverse et al, 2000;Grunewald et al, 2009). Intriguingly, nematodes can influence the polar localization of the PIN proteins, resulting in transport of auxin to the adjacent tissues, as indicated by the redirection of basal localized PIN3 to the lateral plasma membranes (Figure 2) (Grunewald et al, 2009).…”
Section: Nematode Infection Requires Changes In the Host's Auxin Respmentioning
confidence: 99%
“…It was shown by Goverse et al (2000) and Karczmarek et al (2004) that auxin plays a crucial role in the development of nematode feeding sites. They suggested that nematodes are able locally to increase auxin concentration, thus in turn enhancing ethylene production.…”
Section: Plant Hormones Affect Expression Of Atcel2 and Kor3mentioning
confidence: 99%
“…glucanases) but also plant hormones or hormone-related compounds (De Meutter et al, 2005). On the other hand, nematodes are able to alter the hormone homeostasis within feeding sites, as shown by Goverse et al (2000) and later by Karczmarek et al (2004). Both strategies may influence expression of essential genes and thereby support the change from healthy root tissue to a feeding site.…”
Section: Introductionmentioning
confidence: 99%